Pola Asuh Demokratis Orang Tua dan Guru dalam Membentuk Akhlaqul Karimah Anak di Madrasah Diniyah Nurul Furqon: Refleksi Filsafat Pendidikan Islam - Akhmad Afandi; Musta'in (Jurnal Dirosah Islamiyah, 2025)
This study aims to examine the implementation of democratic parenting in shaping children's akhlaqul karimah (noble character) at Madrasah Diniyah Nurul Furqon. Using a qualitative approach with a case study method, data were collected through in-depth interviews, participatory observation, and documentation. The research focuses on three dimensions of child development based on Bloom's Taxonomy: cognitive, affective, and psychomotor. The findings indicate that democratic parenting—characterized by open communication, respect for children’s opinions, modeling, and habituation—significantly contributes to the formation of Islamic character in children. Cognitively, children are able to understand Islamic moral values; affectively, they demonstrate empathy and positive emotional attachment; psychomotorically, they consistently apply moral values in daily behavior. This study strengthens previous findings on the effectiveness of democratic parenting and expands the discussion by highlighting its impact on the psychomotor domain, which is often overlooked. Furthermore, the ta’dib approach from Islamic Educational Philosophy offers a deeper interpretative framework for understanding the character formation process. The study recommends strengthening collaboration between parents and Islamic educational institutions to build a parenting system that aligns with Islamic values.